2022
DOI: 10.1039/d2nr03902h
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression of bacteria by biofilm deterioration using silver nanoparticles with magnetic doping

Abstract: Decades of antibiotic use and misuse have generated selective pressure toward the rise of antibiotic-resistant bacteria, which now contaminate our environment and pose a major threat to humanity. According to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 89 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…143 Additionally, doping metals (Co, Fe, 140 Cu, 141,143 Zn 143 ) could also increase the charge density on the nanoparticles surface, contributing to higher ROS generations. 149 Magnetic behaviors of the nanoparticles (Co, Fe-doped Ag 140 ) mechanically damage the microorganisms, increasing the antimicrobial activity of the magnetic metal-doped nanoparticles. 150 On rare occasions, the antimicrobial properties of doped nanoparticles could be triggered by different stimuli, e.g., light, 141−144 temperature, 114 pH, 143 magnetic field, 140 and catalyst concentration 143,144 (Figure 5).…”
Section: Metal-doped Magnetic Nanoparticles For Antimicrobial Applica...mentioning
confidence: 99%
See 3 more Smart Citations
“…143 Additionally, doping metals (Co, Fe, 140 Cu, 141,143 Zn 143 ) could also increase the charge density on the nanoparticles surface, contributing to higher ROS generations. 149 Magnetic behaviors of the nanoparticles (Co, Fe-doped Ag 140 ) mechanically damage the microorganisms, increasing the antimicrobial activity of the magnetic metal-doped nanoparticles. 150 On rare occasions, the antimicrobial properties of doped nanoparticles could be triggered by different stimuli, e.g., light, 141−144 temperature, 114 pH, 143 magnetic field, 140 and catalyst concentration 143,144 (Figure 5).…”
Section: Metal-doped Magnetic Nanoparticles For Antimicrobial Applica...mentioning
confidence: 99%
“…149 Magnetic behaviors of the nanoparticles (Co, Fe-doped Ag 140 ) mechanically damage the microorganisms, increasing the antimicrobial activity of the magnetic metal-doped nanoparticles. 150 On rare occasions, the antimicrobial properties of doped nanoparticles could be triggered by different stimuli, e.g., light, 141−144 temperature, 114 pH, 143 magnetic field, 140 and catalyst concentration 143,144 (Figure 5). Shujah et al (2022) 32 reported that when MDI was exposed to light irradiation with photon energy, excited electrons get trapped by the molecular oxygen (O 2 ) present on the surface, resulting in production of greater superoxide anion radicals.…”
Section: Metal-doped Magnetic Nanoparticles For Antimicrobial Applica...mentioning
confidence: 99%
See 2 more Smart Citations
“…For this, we stably decorated with Ag/TiO x NPs the surface of chemically resistant polyvinylidene fluoride (PVDF) nanofibrous membranes generated by electrospinning. Although the NPs of each of these elements can separately provide significant improvements like antibacterial behavior, 24 wettability tuning, 25 or self-cleaning properties, 26 when combined, they can additionally provide a more cost-effective solution for large-scale applications because Ti is a more earth-abundant element than Ag. 27 Moreover, as demonstrated in a seminal study, 28 the combination of the two elements enables the formation of chemically active sites leading to better catalytic performance than in the single-element counterparts, thus turning the membranes into catalysts.…”
Section: Introductionmentioning
confidence: 99%